The transregional innovation processes - the key challenge for the trans borders regions - Maria Manuela Natário; Paulo Alexandre Neto (European Regional Science Association (ERSA), 2005)
The competitiveness of regions it is strong linked with innovation dynamics. This dynamics requires the involvement of different actors of the territory, namely, the set of actors with capacity and power to influence the territorial activities: the governance system. Thus, the vigorous attitude and participation of the firms and of institutional associative actors on innovation pressure the innovative performance of the territory. Hence, the aim of this paper is analyse the process of innovation in a transterritorial view and illustrate a perspective of innovation that reflect the better performance innovative of the territory depends of different characteristics of the milieu and evaluate the important conditions for dynamics of innovation. We use the results of survey applied to a vast set of firms and institutional/associative actors for distinguish profiles of involvement in innovation activities and for analyse and perceive which attributes or variables of territory are related with the best performance on innovation. The study looks at five sub regions of the transborder region of central region Portuguese and Spanish: Raia Central Ibérica (three Portuguese and two Spanish).
Keywords: 330